Business Plan ICare Enterprise Beauty and Health Care / Muhd Luqman Abd Aziz ... [et all.] - Abd. Aziz, Muhd Luqman; Che Teh Merican, Syahirul Asyraaf; Hassan, Nurfarina; Mohd Zuki, Nur Natasha; Ruslan, Nur Syafika; Ismail, Nur Hafizah (2019)
Our business concept is to make our product well known in this country. The entrepreneur must know clearly what to do to run and grow its business. It is not only that the way an entrepreneur reacts to the venture that has been proposed that is matter. These things are important to ensure that the business is running properly without any wastage. Furthermore, by analysing the viability of the proposed venture, it will help the sales team to increase their productivity because of a clear mission that they have been exposed to.